In-vitro and in-vivo consequences of mutations in the von Willebrand factor cleaving protease ADAMTS13 in thrombotic thrombocytopenic purpura - Donadelli, Roberta; Banterla, Federica; Galbusera, Miriam; Capoferri, Cristina; Bucchioni, Sara; Gastoldi, Sara; Nosari, Silvia; Monteferrante, Giuseppe; Ruggeri, Zaverio M.; Bresin, Elena; Scheiflinger, Friedrich; Rossi, Edoardo; Martinez, Constantino; Coppo, Rosanna; Remuzzi, Giuseppe; Noris, Marina; the International Registry of Recurrent and Familial HUS/TTP; on behalf of (Thrombosis and Haemostasis, 2006)
Thrombotic thrombocytopenic purpura (TTP) is a disease characterized by microvascular thrombosis, often associated with deficiency of the von Willebrand factor (VWF) cleaving protease ADAMTS13.We investigated the spectrum of ADAMTS13 gene mutations in patients with TTP and congenital ADAMTS13 deficiency to establish the consequences on ADAMTS13 processing and activity. We describe five missense (V88M, G1239V, R1060W, R1123C and R1219W), 1 nonsense (W1016Stop) and 1 insertion (82_83insT) mutations. In two patients no mutation was identified despite undetectable protease activity. Expression in HEK293 mammalian cells (V88M, G1239V, R1123C and R1219W) documented that three missense mutants were not secreted, whereas theV88M was secreted at low levels and with reduced activity. We also provide evidence that impaired secretion of ADAMTS13 mutants observed in vitro translates into severely reduced ADAMTS13 antigen levels in patients in vivo. To evaluate whether the small amounts of mutant protease present in the circulation of patients had VWF cleaving activity, WT and mutant rADAMTS13 were stably expressed in Drosophila S2 cells under the influence of the Drosophila BiP protein signal sequence, which allows protein secretion. Drosophila expression system showed a 40–60% protease activity in the mutants. Several single nucleotide polymorphisms (SNPs) within exons and intron boundaries were found in patients, suggesting that the interplay of SNPs could at least in part account for ADAMTS13 functional abnormalities in patients without mutations. In conclusion, defective secretion and impaired activity of the mutants concur to determine an almost complete deficiency of ADAMTS13 activity in patients with a homozygous or two heterozygous ADAMTS13 mutations.
Keywords: Thrombotic thrombocytopenic purpura; ADAMTS13; mutations; expression studies